The Effect of Automatic Rotational Canal Preparation Technique Compared to the Alternating Technique on the Degree of Curvature in Curved Canals )in Vitro Study) (Journal of Hama University, 2024)
The canals of dental roots are generally characterized by a degree of curvature and the presence of a straight root with a straight canal is exceptional because most natural teeth show curves in their roots, therefore the original shape of the canal must be preserved to maintain the mechanical resistance of the root.Objectives of Research: The study aims to determine the effect of the preparation system on the degree of curvature in curved canals.Materials and Methods: The research sample consisted of 22 recently extracted single-rooted teeth with single canals their length had been standardized to be 16 mm from the apex, then randomly divided into two equal groups (11 teeth for each group) according to the adopted preparation system and the degree of curvature (15-30) as follows: Group I and Group II were fixed with a mixture of acryl, sawdust, and gypsum inside a plastic mold until complete solidification, then a CBCT image was taken pre-preparation and the Schneider method was adopted to measure the degree of curvature for each canal in the longitudinal section (medial-lateral.A CBCT image was taken post-preparation to measure the magnitude of change in the curvature of the canal. The results were analyzed using a Student (T) test for independent samples.The results showed that the alternating preparation system preserved the curvature better than the continuous rotary preparation system, and based on the data it can be concluded that it is preferable to use the alternating system in preparing curved canals.
Keywords: Alternating, continuous rotary, curved canal, Schneider’s method, CBCT image.